Correlation between computer and mathematical literacy levels of 6th grade students - Ic, Unal; Tutak, Tayfun (Eurasian Society of Educational Research, 2018)
Literacy has been defined in the literature frequently. Each new interpretation leads to the idea that the definition can change based on the relevant environment, instruments used and/or the intended objective and there might be different types of literacy including computer literacy, media literacy and visual literacy (Reinking, McKenna, Labbo and Kieffer, 1997; Tuman, 1994). This is also true for computer literacy and mathematical literacy. Therefore, there is a need for studies on computer and mathematical literacy. The objective of the present study was to determine the computer and mathematical literacy levels of secondary school 6th grade students and to reveal the correlation between computer and mathematical literacy levels. The study sample included students that attended provincial, district and village schools, as well as the private schools. The correlation between the computer and mathematical literacy levels of the students that were selected from various regions was determined and the differences based on these levels among the schools were also identified. Since the study aimed to determine the correlation between computer literacy and mathematics literacy of the 6th grade students, relational screening model was utilized in the study. Relational (correlative) studies aim to determine whether there is a correlation between two or more variables (Karasar, 2009). Study population included 139 6th grade students attending a secondary school in Turkey. In the study, “Mathematics Literacy Scale” and “Computer Literacy Scale,” which were developed by the author and tested for validity and reliability were used. The obtained data were analyzed by specific statistical techniques. After the findings were analyzed, results were discussed based on the findings in the literature and necessary recommendations were presented. © 2018 Public Library of Science. All rights reserved.
Keywords: Computer literacy; Literacy; Mathematics literacy